Coronary Computed Tomography Angiography Analysis of Calcium Content to Identify Non-culprit Vulnerable Plaques in Patients With Acute Coronary Syndrome - Pezel, Théo; Sideris, Georgios; Dillinger, Jean-Guillaume; Logeart, Damien; Manzo-Silberman, Stéphane; Cohen-Solal, Alain; Beauvais, Florence; Devasenapathy, Niveditha; Laissy, Jean-Pierre; Henry, Patrick (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: Aside from the culprit plaque, the presence of vulnerable plaques in patients with acute coronary syndrome (ACS) may be associated with future cardiac events. A link between calcification and plaque rupture has been previously described. AIM: To assess whether analysis of the calcium component of coronary plaques using CT angiography (CCTA) can help to detect additional vulnerable plaques in patients with non-ST elevation myocardial infarction (NSTEMI). MATERIALS AND METHODS: Cross sectional study of consecutive patients referred for NSTEMI from 30 July to 30 August 2018 with CCTA performed before coronary angiography with systematic OCT analysis of all coronary arteries within 24 hours of clinical onset of NSTEMI. Three types of plaques were defined: culprit plaques defined by angiography (vulnerable culprit plaques–VCP) – plaques with a fibrous cap thickness <65 microns or thrombus in OCT (vulnerable non-culprit plaque–VNCP) – plaques with a fibrous cap thickness ≥65 microns in OCT (stable plaque–SP). RESULTS: A total of 134 calcified plaques were identified in 29 patients (73% male, 59±14 years) with 29(22%) VCP, 28(21%) VNCP and 77(57%) SP. Using CCTA analysis of the calcium component, factors associated with vulnerable plaques were longer calcification length, larger calcification volume, lower calcium mass, higher Agatston score plaque-specific (ASp), presence of spotty calcifications and an intimal position in the wall. In multivariate analysis, ASp, calcification length and spotty calcifications were independently associated to vulnerable plaques. There was no difference between VCP and VNCP. CONCLUSIONS: CCTA analysis of calcium component of the plaque could help to identify additional vulnerable plaques in NSTEMI patients.